Research of changes in the level of vascular endothelial growth factor in experimental diabetic retinopathy. comparison of methods of correction - Sirman, Ya.; Savytskyi, I. (Journal of Education, Health and Sport, 2021)
The aim of work to investigate the changes in the vascular endothelium growth factor in experimental animals, which were simulated diabetic retinopathy and against the background of its correction. The results of the analysis of the vascular growth factor in the 2nd group confirm the development of diabetic retinopathy, a particularly pronounced increase in the marker was detected on the 180th day of the development of the pathological process. It was established analyzing the data of group No. 3 that the correction of the pathological condition with hypoglycemic agents has partial positive effect but requires the involvement of additional means of correction in addition to the normalization of the level of glycemia. The results of the 4th group indicate that the involvement of a nitric oxide donor and aflibercept in the correction of diabetic retinopathy has positive effect on the reduction of the level of vascular growth factor, more pronounced compared to the 3rd group, but it does not reach normative values. It is observed that the correction of the simulated pathological condition by reducing hyperglycemia, administration of aflibercept and bromfenac (group No. 5) gives positive results, but less pronounced, compared to the data of the 4th group. It was found that in rats in which diabetic retinopathy was modeled with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac (group No. 6) at the first stage, there is a pronounced effectiveness of the proposed method of correction in comparison with the previously considered methods, the established positive trend is being followed also at the 2nd and 3rd stages of the experiment, which indicates the effectiveness of this correction method. The most pronounced positive effect of normalizing the level of vascular growth factor is observed when using a hypoglycemic drug in combination with the administration of aflibercept, a solution of L-arginine and citicoline (in group No. 7).